Portal Hypertension: 2 years Experience in Department of Pediatric Gastroenterology and Nutrition, at a Tertiary Care Hospital, Bangladesh - Hussain, Faika; Karim, ASM Bazlul; Matin, Abdul; Sultana, Kaniz; Anwar, Syeda Afria (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Portal hypertension is a clinical syndrome defined by a pathologic increase of portal venous pressure. The objectives of this study were to evaluate etiological and clinical presentation of portal hypertension admitted in a tertiary care centre of Bangladesh. Materials and Methods: This cross sectional study was done at the Department of Paediatric Gastroenterology & Nutrition, BSMMU on 100 consecutive cases admitted during the period from July 2013 through June 2015. Confirmation of the presence of portal hypertension was done by demonstration of oesophageal varices during upper GI endoscopic examination. The diagnosis of chronic liver disease was based on a combination of clinical, biochemical (abnormal liver function tests) and ultrasonographic (coarse echotexture of liver) features. Extrahepatic portal hypertension was diagnosed on the basis of clinical, normal liver function test and ultrasonographic evidence of portal or splenic vein thrombosis, with or without cavernous transformation. Doppler ultrasound showed increase portal venous pressure. Results: Patient's age group was 2 to 15 years. 69 cases were extra hepatic portal hypertension. Haematemesis and/or melaena were found in 42(60.9%) and splenomegaly was found in 68(98.6%) cases. Of extra hepatic 69 cases 10% had history of umbilical sepsis. Of the 31cases of CLD with portal hypertension, haematemesis and/or melaena was found in 20(64.5%) cases, splenomegaly in 30(96.8%), ascites 8(25.8%).Most (50%) of CLD cases were cryptogenic followed by Wilsons disease 29%. Of the 100 cases, endoscopy revealed grade 3 esophageal varices in 45% cases. All the patients were treated with propranolol. EVL was done in 70% cases. Conclusion: In this study, most of the cases were extra hepatic portal hypertension. Gastrointestinal bleeding & splenomegaly were found in most of the cases. No risk factor was found in most of extra hepatic cases. Portal vein thrombosis & cryptogenic were the most common cause in extra-hepatic and intra-hepatic cases respectively. J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 26-29